Математичні моделі підйомних установок як об'єктів електромеханічних систем автоматичного керування - Попович, Микола Гаврилович; Сергієнко, Олег В'ячеславович (НТУ "ХПІ", 2010)
Mathematical models of elevating mechanisms in view of elasticity of ropes and a backlash in a reducer are presented. It will allow to synthesize system with high accuracy of positioning.
Mathematical models of elevating mechanisms as objects of electromechanical systems of automatic control
Keywords: ланцюг кінематичний; канат врівноважувальний; зазор механічний